Partial purification and properties of CTP:phosphatidic acid cytidylyltransferase from membranes of Escherichia coli. - Langley, K E (1978)
The cytosine liponucleotides CDP-diglyceride and dCDP-diglyceride are key intermediates in phospholipid biosynthesis in Escherichia coli (C. R. H. Raetz and E. P. Kennedy, J. Biol. Chem. 248:1098--1105, 1973). The enzyme responsible for their synthesis, CTP:phosphatidic acid cytidylytransferase, was solubilized from the cell envelope by a differential extraction procedure involving the detergent digitonin and was purified about 70-fold (relative to cell-free extracts) in the presence of detergent. In studies of the heat stability of the enzyme, activity decayed slowly at 63 degrees C. Initial velocity kinetic experiments suggested a sequential, rather than ping-pong, reaction mechanism; isotopic exchange reaction studies supported this conclusion and indicated that inorganic pyrophosphate is released before CDP-diglyceride in the reaction sequence. The enzyme utilized both CTP and dCTP as nucleotide substrate for the synthesis of CDP-diglyceride and dCDP-diglyceride, respectively. No distinction was observed between CTP and dCTP utilization in any of the purification, heat stability, and reaction mechanism studies. In addition, CTP and dCTP were competitive substrates for the partially purified enzyme. It therefore appears that a single enzyme catalyzes synthesis of both CDP-diglyceride and dCDP-diglyceride in E. coli. The enzyme also catalyzes a pyrophosphorolysis of CDP-diglyceride, i.e., the reverse of its physiologically important catalysis.